3D non-linear finite element analysis of concentrically loaded high strength reinforced concrete column with GFRP bar - Adhi Dharma Prasetyo; Bambang Piscesa; Harun Al Rasyid; Dwi Prasetya (Institut Teknologi Sepuluh Nopember, 2020)
The use of High Strength Concrete (HSC) material in Reinforced Concrete (RC) column has become widely used. HSC was found to be durable, strong in compression, but it has low ductility. This low ductility of HSC can be improved by providing confinement. However, for HSC with concrete strength higher than 70 MPa, additional clause for confinement in ACI 318-19 generates denser arrangement of transverse bars and eventually creates weak planes between the concrete core and the cover. These weak planes can trigger early cover spalling. To reduce the utilization of confining bars, high-strength Glass Fiber Reinforce Polymer (GFRP) bar can be used. However, the performance of GFRP bar varies significantly from their uniaxial behavior in tension or compression to the real performance when it is used as the main reinforcement. For that reason, this paper tries to investigate the behavior of HSC RC column with bars made of conventional steel rebar and with GFRP bars. Due to limited data on the strain gauge reading on the GFRP bars from the available test result, an inverse analysis is carried out to determine the best stress-strain curve for GFRP bars used as the main reinforcement. For that purpose, an inhouse finite element package called 3D-NLFEA is used. From the comparisons, it was found out that the peak load, softening behavior, and the concrete core enhancement prediction agrees well with the test result. From the inverse analysis, only 25% and 45% of the GFRP bar yield strength can be deployed when loaded under compression and tension, respectively.